Tourist’s preference in selection of a restaurant: testing mediating role of service quality - Rahman, Muhammad Sabbir; Fadi Abdel Muniem Abdel , Fattah (2014)
The aim of this research is to examine in what extent tourists’ preferences, and their satisfaction relates to their purchase intention from a restaurant. The study also considers the mediating role of service quality among the relationships. In order to test the hypothesized model, this study used a sample of 180 tourists’ who were visited in Malaysia. The instruments were developed through the measures adapted from previous scholarly works. In addition, structural equation modeling was applied to test the proposed model. The results show that the relationships among the variables are all significant except one. Moreover, the mediating effect of service quality in between tourists’ preference and purchase intention is partial. On the other hand, the role of service quality as mediator in between the relationship between tourists’ satisfaction and their purchase intention from a restaurant was full rather partial. This study offers valuable insights for restaurant managers to aware of and to deliver consistent and attractive services to their customers by considering their preference and satisfaction through appropriate service quality components. This research contributes to the literature on tourism marketing by examining their preferences and satisfaction in choosing a restaurant. Above all, this research also used service quality as a mediating variable in between the relationship among tourist’s preferences, satisfaction towards their intention to purchase from a restaurant which is scared in the tourism marketing literature under the Malaysian tourism industry context.